2016
DOI: 10.2174/1389557516666160611015815
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Anti-inflammatory Potential of Pyridazinone Derivatives

Abstract: Pyridazinone and its derivatives have various ranges of biological and pharmacological activities including anti-inflammatory, antifeedant, anticonvulsant, antidiabetic, herbicidal, antihypertensive, antiplatelet, antifungal, antibacterial, anticancer and antiviral activities. Pyridazinone magic moiety has allowed the generation of a huge number of structurally different derivatives. Most of the pyridazinone derivatives are derived from substitution of the pyridazinone oxygen, nitrogen and C4/C5/C6 carbon posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 0 publications
0
25
0
Order By: Relevance
“…The pyridazinone nucleuses which are serve as therapeutic agents as nonsteroidal antiinflammatory drugs. This nucleus has a wide spectrum in bioorganic and medicinal chemistry and application in drug discovery (Saini at al., 2016). The aryl-pyridazinonesubstituted benzenesulphonylurea derivatives were tested for their anti-hyperglycaemic activity in glucose-fed hyperglycaemic normal rats.…”
Section: Biological Activitiesmentioning
confidence: 99%
“…The pyridazinone nucleuses which are serve as therapeutic agents as nonsteroidal antiinflammatory drugs. This nucleus has a wide spectrum in bioorganic and medicinal chemistry and application in drug discovery (Saini at al., 2016). The aryl-pyridazinonesubstituted benzenesulphonylurea derivatives were tested for their anti-hyperglycaemic activity in glucose-fed hyperglycaemic normal rats.…”
Section: Biological Activitiesmentioning
confidence: 99%
“…The pyridazinone structure serves as a potential scaffold for the development of novel anti-inflammatory drugs [11,12]. For example, some pyridazinone derivatives have been reported to inhibit cyclooxygenase 2 (COX2) [13,14]; thus, they belong to the group of nonsteroidal anti-inflammatory drugs (NSAID).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, pyridazinone derivatives have received substantial attention due to their extensive biological activities. For example, they have been described as anti-inflammatory (Mogilski et al 2015; Saini et al 2016), analgesic (Mogilski et al 2015), anti-viral (Wang et al 2015), anti-parasitic (Jacomini et al 2016), anti-microbial (Faidallah et al 2013), antidiabetic (Rathish et al 2009), anti-cancer (Jin et al 2015; Zhou et al 2014), anti-tubercular (Li et al 2014), as protein kinase inhibitors (Dorsch et al 2015; Elagawany et al 2013; Liu et al 2016), and have also been shown to affect the cardiovascular system (Asif 2015; Costas et al 2015), among others.…”
Section: Introductionmentioning
confidence: 99%